Saving gas through cross-border renewable and nuclear electricity generation - Christoph Halser; Dogan Keles; Florentina Paraschiv (Environmental Research Letters)
In fossil fuel-driven electricity markets, gas power plants are mostly the price setting technology in peak demand hours. At the same time, gas technology has the role of balancing out the volatility of increasing shares of intermittent renewable generation. This interdependence, coupled with recent fears of supply shortages, raises the question how gas-fired generation can be replaced with carbon-free technologies. Controlling for fundamental supply and demand in the interconnected markets, we quantify the effect of intermittent renewable and nuclear generation in neighboring markets on the use of natural gas for electricity generation in Germany. Findings indicate that cross-border intermittent wind, PV, and nuclear generation significantly reduce the need for German gas. We further show Germany’s dependency on French cross-border nuclear energy to supplement the gas unavailability during the gas crisis period. We argue for larger market coupling and flexible generation alternatives and adaptive demand solutions including cross-border capacities for substituting gas when renewable generation is low across Europe.